Piaractus mesopotamicus gonad differentiation - Barbosa, Roosevelt Passos [UNESP]; Kuradomi, Rafael Yutaka [UNESP]; Sato, Rafael Tomoda [UNESP]; Batlouni, Sergio Ricardo [UNESP] (Hindawi, 2022)
In this study, we evaluated the pacu (Piaractus mesopotamicus) gonadal differentiation process from zero to 299 days after eclosion (DAE). To that end, individuals were subjected to 5 samplings (96, 123, 150, 233 and 299 DAE) for evaluation of the gonadal differentiation process through histological analysis. The gonads were recognized macroscopically from 96 DAE and were undifferentiated up to 123 DAE. Differentiation into ovaries was first observed at the 150 DAE sampling (average total length = 10.03 ± 0.12 cm and average total biomass = 18.21 ± 1.22 g). We observed a great heterogeneity of sizes in the fish analysed up to 299 days. At the end of the experiment, only 11/51 animals analysed had gonads differentiated into ovaries, and the process occurred in a large window. Sex differentiation into testis was not observed. This study also showed that larger and more aggressive fingerlings that occupied the front part of earthen ponds, popularly known in Portuguese as cabeceiras, were not necessarily females, as previously believed due to their larger size. Thus, we did not observe sexual dimorphism up to 299 DAE, but since it is known that in adult females of this species do reach larger sizes, future approaches need to show whether differentiated growth rates between genera occur before slaughter size, thus justifying the production of single-sex populations.
Keywords: gonad; monosex production; pacu; sexual size dimorphism